Zohlednění bezpečnostních rizik v současném územním plánování v České republice - Šilhánková, Vladimíra; Pondělíček, Michael (Univerzita Pardubice, 2010)
The questions of territorial security could be dealt with in urban planning tasks. The contemporary situation in the Czech Republic is such that security issues are understood as being very low. Our planning legislation neglects the protection of critical infrastructure and also fails to answer the majority of territorial security questions. This paper is focused on these very important and currently unsolved and disseminated problems.
Keywords: security; legislation; critical infrastructure; urban area; urban planning